Inverse association of dietary consumption of n3 and n6 fatty acids with hyperuricemia among adults. - Huakai Wang; Chao Zhang; Yuxin Sun; Sirui Sun; Zhe Wang; Honggang Xiang (PLoS ONE)
Background The precise link between dietary consumption of n-3 and n-6 fatty acids and hyperuricemia remains equivocal. Accordingly, the purpose of the current investigation is to clarify any possible associations between the consumption of n-3 and n-6 fatty acids and hyperuricemia in the context of American adults. Materials and methods The present investigation employed a cross-sectional design, comprising a sample of 21,120 American adults above the age of 20 from the National Health and Nutrition Examination Survey (NHANES) waves between 2007 and 2016. The dietary consumption of n-3 and n-6 fatty acids was measured through two 24-h dietary recall interviews. To assess the relationships of dietary consumption of n3 and n6 fatty acids with hyperuricemia, we applied multivariable logistic regression, t tests, chi-square tests, and restricted cubic spline. To determine the robustness of our findings, sensitivity analyses were also carried out. Results The results of the multivariable logistic regression models indicated a significant correlation between dietary consumption of n3 and n6 fatty acids and hyperuricemia. The ORs with 95% CIs of hyperuricemia for the highest tertile versus lowest tertile of dietary consumption of n3 and n6 fatty acids were 0.76 (0.66, 0.88) (p < 0.001) and 0.72 (0.64, 0.82) (p < 0.001), respectively. Moreover, dose‒response analyses revealed a linear relationship between n-3 and n-6 fatty acid consumption and the risk of hyperuricemia. Conclusion The findings of this study indicate a significant inverse correlation between the dietary consumption of n3 and n6 fatty acids and hyperuricemia in the US adult population. Notably, there was no significant relationship between the n6:n3 ratio and hyperuricemia.